2020
DOI: 10.1017/ice.2020.1243
|View full text |Cite
|
Sign up to set email alerts
|

Extended use or reuse of single-use surgical masks and filtering face-piece respirators during the coronavirus disease 2019 (COVID-19) pandemic: A rapid systematic review

Abstract: Background: Shortages of personal protective equipment during the COVID-19 pandemic has led to the extended use or re-use of single-use respirators and surgical masks by frontline healthcare workers. The evidence base underpinning such practices warrants examination. Objectives: To synthesise current guidance and systematic review evidence on extended use, re-use, or reprocessing of single-use surgical masks or filtering facepiece respirators. Data sources: World Health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 21 publications
0
43
0
1
Order By: Relevance
“…There are three common problems the UV-C sterilization process demonstrates: the possibility of thermal deformation, shadowing, and absorption effects [ 4 , 5 , 8 , 27 , 31 ]. As the first potential problem (changes in integrity) already discards reprocessed SUPPE, we opted to leave it on Table 1 column “Changes in integrity or fit.” From our SLR database, 30 studies (51.72%) assess it, of which 21 [ 33 , 35 , 37 , 40 , 44 , 48 , 49 , 51 , 53 , 61 , 62 , 64 , 65 , 67 , 70 , 71 , 73 , 80 , 81 , 82 , 87 ] observe no physical changes within different rounds of sterilization or extenuating conditions.…”
Section: Uv-c’s Disadvantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three common problems the UV-C sterilization process demonstrates: the possibility of thermal deformation, shadowing, and absorption effects [ 4 , 5 , 8 , 27 , 31 ]. As the first potential problem (changes in integrity) already discards reprocessed SUPPE, we opted to leave it on Table 1 column “Changes in integrity or fit.” From our SLR database, 30 studies (51.72%) assess it, of which 21 [ 33 , 35 , 37 , 40 , 44 , 48 , 49 , 51 , 53 , 61 , 62 , 64 , 65 , 67 , 70 , 71 , 73 , 80 , 81 , 82 , 87 ] observe no physical changes within different rounds of sterilization or extenuating conditions.…”
Section: Uv-c’s Disadvantagesmentioning
confidence: 99%
“…The chemical methods have some cons, such as their residues causing allergic reactions and having an intense odor. They depend on specific machinery, and VH 2 O 2 is highly unstable when vaporized, losing significant efficiency when condensed [ 3 , 5 , 7 , 9 , 12 , 25 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the cited argument that extended use avoids the risk of selfcontamination during repeated donning and doffing seems plausible. 35 The use of homemade cloth masks of different fabrics has been studied as an alternative means to mitigate the challenges of shortages of surgical masks. A randomized control study comparing cloth masks with surgical masks found that cloth masks may increase the risk of infections possibly because of their reuse, moisture retention, and poor filtration.…”
Section: Questionsmentioning
confidence: 99%
“…by multiplicatively reducing the β parameters in different locations. There is a significant body of literature on the effectiveness of mask wearing, including differences based on the material of the mask and the locations in which they are worn [54, 55, 56], as well as changes in efficiency due to re-using or washing them [57, 58]. In general, we focus on the wearing of masks by non-healthcare workers in settings outside the home and estimate mask effectiveness, E , to be 50% [59], irrespective of the specific of the location.…”
Section: Mitigation Policies and Strategiesmentioning
confidence: 99%